Improvement of biocorrosion resistance and antibacterial performance of Ti-3Cu alloy subjected to laser shock peening. (February 2023) - Yang, Yuling; Lu, Ying; Shi, Wanru; Hou, Baoping; Qiao, Hongchao; Qi, Jinyan; Zhang, Erlin; Qin, Gaowu
Highlights: Laser shock peening (LSP), a novel surface processing technique, was introduced to improve the surface related properties of Ti-3Cu alloy. The refinement in grain size and presence of Ti2 Cu and TiCu2 subjected to LSP enhanced the wettability of the surface. The surface corrosion resistance and antibacterial properties were significantly enhanced by LSP treatment. Abstract: Ti-Cu alloys have attracted much attention in the field of orthopedics and dentistry. The existence form of Cu is a main factor influencing the bacterial response and corrosion resistance. Laser shock peening (LSP) is increasingly applied as an effective technology for enhancing the properties, especially the corrosion resistance of different metallic components. Present work is focused on the examination of the effects of LSP treatment on the phase constituents, microstructure and surface grain size of the samples, and the relevant surface related properties such as wetting behavior, bio-corrosion resistance to SBF solution, and antibacterial performances against S . aureus. The results show that the refinement in grain size and presence of Ti2 Cu and TiCu2 subjected to LSP enhanced the wettability of the surface. The application of LSP treatment is seen to significantly improve the surface corrosion resistance, reduce the adhesion of bacteria and in turn enhance the antibacterial properties of the wrought Ti-3Cu alloys.